THE POPULATION EXPLOSION PROBLEM IN INDIA- CAUSES, EFFECTS AND SOLUTIONS - Smt Gayatri Sunkad, (European Journal of Life Safety and Stability (2660-9630), 2021)
The population explosion is the major economic problem in India. In the world, India is the second, biggest populated country in the world. According to 2011 census, we had reached more than 121 crore population in India. India is the seventh largest country in the world. The population explosion is the biggest obstacle in the way of our country’s economic development. The population explosion is itself is an economic problem and time it also leads to the social problems in India also. It influences so many factors like social development, health, hygiene, education, national income etc. Population is having the two factors like quality and quantity. If any country’s population is having less quality and high in quantity, then it may become burden to the nation. If any country is having less in quantity and high is quality, then certainly, it become boon to the nation. But if we are taking the steps to control the population explosion, then only we can reach our expected goal of development.